PENGARUH MODEL PEMBELAJARAN DAN KEGIATAN PRAKTIKUM TERHADAP PEMAHAMAN KONSEP PESERTA - Niken Oktaviani; Nabilla Rida Tri Nisa; Yayang Ade Suprana; Try Annisa Lestari (MEMACE: Jurnal Linguistik, Pendidikan Bahasa Indonesia, dan Asing, 2024)
This study aims to determine the influence of learning models and practicum activities on students' conceptual understanding, as well as to examine the interaction between learning models and practicum activities on students' conceptual understanding. The research was conducted using a quantitative descriptive method with a 3x2 factorial experimental design, and the data were analyzed using two-way ANOVA to identify differences in variance between two treatment groups. Based on the analysis results, it can be concluded that there is an effect of learning models on students' conceptual understanding. However, there is no effect of conducting practicum activities either at the beginning or at the end of the learning process on students' conceptual understanding. Additionally, there is no interaction between learning models and practicum activities, as practicum activities are considered part of the learning model. The discrepancy between the results and theoretical expectations is influenced by several factors, including students' initial understanding and skills in conducting practicum activities. Furthermore, inaccurate time estimation in executing each step of the learning syntax also contributed to these findings.